LITERATURE REVIEW ON OVERSIGHT AND ACCOUNTABILITY IN POLITICAL BUDGET MANAGEMENT - Loso Judijanto; Ani Kusumaningsih; Adih Supriadi (RADJA PUBLIKA, 2025)
Oversight and accountability are fundamental elements in political budget management that serve to ensure transparency, prevent misuse of funds, and improve efficiency in budget allocation. This literature review explores how effective oversight and accountability mechanisms can influence the quality of budget management, drawing on various academic studies and international reports. The literature indicates that oversight involving civil society, the media, and information technology can strengthen openness, while accountability mechanisms such as audits and periodic reporting are key tools for maintaining political integrity. However, challenges such as political resistance, lack of capacity in oversight institutions, and low public awareness remain significant obstacles. Based on this analysis, structural reforms and cross-sectoral collaboration are essential to enhance the effectiveness of oversight and accountability in political budget management, thereby building public trust and ensuring the sustainability of a more responsive and transparent political system.